An overview of Covid-19 patients with and without comorbid Diabetes Mellitus at Surabaya Hajj general hospital - Uswatun Hasanah; Endang Darmawan; Sugiyarto Sugiyarto (Universitas Ahmad Dahlan, 2022)
Diabetes mellitus (DM) is one of the most common comorbidities found in patients infected with Covid-19 with severity and death. To obtain an overview of Covid-19 patients with and without comorbid DM. A retrospective cohort study, taking subjective data on Covid-19 patients with and without DM at Surabaya Hajj general hospital for the period of March 2020 to June 2021. Data analysis using the Chi-square test was to determine differences in both test variables. The death of Covid-19 patients with comorbid DM was found with the condition in which the average random blood glucose (RBG) increased by >150 mg/dl (286 mg/dl), as well as in recovered patients (197 mg/dl); meanwhile, patients without comorbid DM died with also an increase in the RBG value (166 mg/dl). Male patients were found to be more prone to get infected with Covid-19 than female patients. It can be concluded that there was no significant difference in the severity of cases in Covid-19 patients with comorbid DM and without comorbid DM. Deaths due to Covid-19 in patients with comorbid DM or without comorbid DM occurs due to the increasing blood glucose value by >150 mg/dl.